2017
DOI: 10.3917/inno.pr1.0017
|View full text |Cite
|
Sign up to set email alerts
|

Le système national d’innovation dans les pays du Maghreb : entre failles structurelles et besoin de coordination et de gouvernance appropriées

Abstract: Dans les théories économiques et de gestion, l’innovation est souvent considérée comme source de croissance. Dans une perspective d’analyse de l’innovation, sous l’angle des systèmes nationaux d’innovation (SNI), cet article tente d’expliquer les raisons de la faiblesse ainsi que de la fragmentation des SNI des pays du Maghreb. L’analyse montre une faiblesse structurelle combinée avec une faiblesse au niveau de la coordination institutionnelle et un manque d’efficacité des actions des pouvoirs publics. En s’ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Thus, the Algerian NIS is characterized by institutional and structural dysfunctions (Ben Slimane and Ramadan, 2017;Djeflat, 2003). These authors have shown that the reasons for the failures of the NIS are related to a structural weakness combined with a weakness in institutional coordination and a lack of effectiveness of the actions of the public authorities.…”
Section: Current Situation Of Nismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the Algerian NIS is characterized by institutional and structural dysfunctions (Ben Slimane and Ramadan, 2017;Djeflat, 2003). These authors have shown that the reasons for the failures of the NIS are related to a structural weakness combined with a weakness in institutional coordination and a lack of effectiveness of the actions of the public authorities.…”
Section: Current Situation Of Nismentioning
confidence: 99%
“…Despite the rather encouraging indicators of research activities within the academic sphere in Algeria, all research studies in this area have found that vertical collaborations, ie the flow of information and knowledge between the world of research and the actors of the innovation system remain weak (Haudeville and Younes Bouacida, 2020;Younes Bouacida, 2018;Ben Slimane and Ramadan, 2017;Amdaoud, 2016;Djeflat, 2009). Indeed, the global ranking of the Global Index of Innovation 2018 highlights the weakness of vertical collaborations and the lack of the impact of knowledge in Algeria since it is positioned for these two indicators at the bottom of the table (at the 111th and 101st respectively).…”
Section: Vertical Collaborationsmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est cette absence de liens et de connexions qui est globalement mise en exergue dans la littérature sur les S.N.I. en développement (Szogs et al, 2011 ;Djeflat, 2016 ;Ben Slimane et Ramadan, 2017).…”
Section: Pertinence Du Conceptunclassified
“…Ainsi, pour développer la filière anacarde, il est nécessaire de s'assurer que les acteurs de premier rang que sont les producteurs disposent de tous les moyens et connaissances nécessaires afin de pouvoir adopter des comportements qui conduisent u changement au sein de leurs exploitations ou à innover. Aujourd'hui, la fourniture des services supports à l'innovation est le principal objectif que visent les projets de développement dans une perspective de facilitation du processus d'innovation (Ben Slimane et al, 2017). Parmi les services supports à l'innovation, le plus important et fondamental aujourd'hui, est basé sur le renforcement de capacités .…”
Section: Introductionunclassified